Analysis Of Service Quality And User Acceptance Of BMKG Info Application Using EgovQual Model And Technology Acceptance Model (TAM) In Central Java - Adi, Wahyu Prasetya; Supriyanto, Aji (Information Technology International Journal, 2025)
This study analyzes the service quality and user acceptance of the Info BMKG application in Central Java, integrating the e-GovQual model and the Technology Acceptance Model (TAM). Using a quantitative survey of 239 Info BMKG users, data was analyzed with PLS-SEM. Findings show the measurement model is highly reliable and valid. Seven of nine hypothesized relationships were statistically significant and positive. Specifically, Perceived Ease of Use (PEOU) significantly influenced both Behavioral Intention to Use (BIU) and Perceived Usefulness (PU). Perceived Usefulness (PU) also significantly impacted Behavioral Intention to Use (BIU). Behavioral Intention to Use (BIU) significantly affected Actual System Use (ATU). For user satisfaction (SAT), Reliability (REL) and Citizen Support (SUP) had a significant positive influence. Actual System Use (ATU) also significantly influenced Satisfaction (SAT). However, the direct influence of Efficiency (EFF) and Trust (TRU) on Satisfaction (SAT) was not statistically significant. These results support the conceptual model and offer valuable insights for enhancing digital public services.. A similar phenomenon is seen in the impact of Trust (TRU) on Satisfaction (SAT), where the high p-value (0.804) and low t-statistic (0.248) indicate that this relationship is also not statistically significant.